Sixth state reform in Belgium: New, but not the last stage of devolution - Stanković Marko (Anali Pravnog Fakulteta u Beogradu, 2014)
Belgian Constitution of 1831 is one of the oldest constitutions in the world which is still in force. It is well known for having remained in force despite the change of organization of state - from unitary to federal. Starting from the 1970s, six state reforms were conducted in Belgium, and the monarchy was transformed from centralized unitary state into a decentralized federation. Pressures for further devolution are getting stronger, and some of the members of the Flemish community have clearly expressed their desire for independence from the Kingdom of Belgium and the establishment of their own state. This paper in its first part analyzes five previously conducted reforms of Belgian constitutional system. The second part deals with changes agreed in so-called Butterfly agreement and implemented in sixth state reform. In the end, author is trying to anticipate possible epilogues of state crisis, which takes almost a decade.